Effects of sequence and length on imino proton exchange and base pair opening kinetics in DNA oligonucleotide duplexes. - Leijon, M (1992)
The base catalysed imino proton exchange in DNA oligonucleotides of different sequences and lengths was studied by 1H-NMR saturation recovery experiments. The self-complementary sequences studied were GCGCGAATTCGCGC (I), CGCGAATTCGCG (II), GCGAATTCGC (III), and CGCGATCGCG (IV). The evaluation of base pair lifetimes was made after correction for the measured 'absence of added catalyst' effect which was found to be characterized by recovery times of 400-500 ms for the AT base pairs and 250-300 ms for the GC base pairs at 15 degrees C. End effects with rapid exchange is noticeable up to 3 base pairs from either end of the duplexes. The inner hexamer cores GAATTC of sequences I-II show similar base pair lifetime patterns, around 30 ms for the innermost AT, 5-10 ms for the outer AT and 20-50 ms for the GC base pairs at 15 degrees C. The shorter sequences III and particularly IV show much shorter lifetimes in their central AT base pairs (11 ms and 1 ms, respectively).